Pengaruh I-Branding pada Website Binus University terhadap Loyalitas Pelanggan - Meyliana Meyliana; Henry Antonius E.W.; Stephen W. Santoso (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Implementing an appropriate branding strategy supports a company in putting its product or service to be customers’ top of mind. Aligned with the development of information technology, especially the Internet, merging branding with internet (i-branding) creates a unique characteristic for a company. It is very helpful for a company in competing in the free market. Therefore, it is important for a company to know information about customer perception in assessing i-branding that has been applied to its website. As an educational institution which is a pioneer in the use of information technology, Binus University concerns much about its branding on the official website (www.binus.ac.id). This study is conducted to assess the i-branding of Binus University on the point of view of its students as customers. This study uses Four Pillars of i-branding consisting the following variables: customer understanding, marketing communication, interactivity, content, and customer loyalty consisting of trust and satisfaction. The hypothesis is tested by correlation analysis and regression analysis. Based on correlation analysis, all hypotheses of H1 (no relation) is received and based on regression analysis,all hypotheses of H1 (bring effects) is received.